A voz do paraíso: Um estudo interpretativo da comicidade sobre a representação de Eleutério, um personagem contador de “causos”, na telenovela Paraíso de 2009 - Coelho, Thiago Henrique Fernandes (2020)
The objective of this work is to investigate the representation of the caipira culture and its relation with the comedy in the soap operas, through the analysis of the representation of the storytelling character Eleutério Ferrabrás, played by the actor Reginaldo Faria, in the soap opera Paraíso (2009). Seeking to analyze his performance as a “storyteller” based on the studies by Luciana Hartmann (2011) on the performance of “storytellers” on the border between Brazil, Uruguay and Argentina. As the “causes” of Eleutério greatly affect the lives of the characters in the soap opera, generating many comical situations, analyzes of the comic scenes that the “causes” cause were made, based on the theories of Henri Bergson (2001) and Vladimir Propp (1992), who formulated concepts to analyze the comic, how it occurs, its causes, the different types of laughter, etc. The choice of this soap opera is based on the fact that the author of soap operas Benedito Ruy Barbosa, constantly portrays characters linked to the countryside in his works, either as presenting the context of the farm as a nucleus, or presenting all the plot and plot around the interior issues. The technique of qualitative approach to the material was based on the appreciation of the soap opera chapters, and using as selection criteria, the scenes with greater comic content in relation to the “causes” of Eleutério, as well as the scenes that he tells his “causes”. The methodology used was cartographic with content analysis by Bardin (2000). The way to collect the data was through the transcription of scenes from the chapters trying not to interfere in the way the characters speak, making a spontaneous writing based on the spelling proposal made by Hartmann (2011). The collected data show that it is possible to arrive at the following synthesis by means of four supposedly creative and creative words: the voice, the hands, the humor and the camera, which are present in the interpretation of the storytelling character Eleutério, played by the actor Reginaldo Faria. The voice and hands were the body resources most used by actor Reginaldo Faria during the storytelling. The camera, on the other hand, having an interpretive adaptation in accordance with the technological equipment, which is designed for this medium, with the use of plans, the overlay of images, while the character told the stories, the actions of the characters of the story were shown, leaving only the voice off of the accountant, with periodic cut to show the same accountant narrating the story.